Integrasi Data Penelitian dan Pengabdian Dosen untuk Monitoring Berbasis Data Warehouse - Yunita Amalia; Nahrun Hartono; Asrul Azhari Muin (System Information and Computer Technology (SYNCTECH), 2026)
The management of research and community service data of lecturers in higher education institutions requires an integrated system to support effective monitoring and reporting processes. At UIN Alauddin Makassar, research and community service data had previously been stored separately in Microsoft Excel files managed by different staff members, which made data processing, retrieval, and comprehensive analysis difficult. This study employed a quantitative approach with stages consisting of requirements analysis, system design, data warehouse implementation, and system testing. Data integration was carried out through the Extract, Transform, and Load process into a structured centralized data storage. System testing was conducted using the Black Box Testing method to ensure that all system functions operated according to user requirements. The results showed that the implementation of the data warehouse successfully integrated research and community service data in a structured manner, reduced data duplication, and improved efficiency in data retrieval and report generation. The developed system also provided monitoring reports in the form of a web-based dashboard that was informative and easy to understand. Therefore, the implementation of this data warehouse was able to assist the Institute for Research and Community Service (LP2M) in managing and monitoring lecturers’ research and community service activities more effectively and optimally.